Conversational Implicature in the Animated Film “Up” - Amiril Achmed; Amalia Hasan (Journal of Social, Culture, and Language, 2026)
Communication in human interaction often involves meanings that are not explicitly stated but inferred through context, a phenomenon known as conversational implicature. This study examines conversational implicature in the animated film “Up” (2009), focusing on the dialogues of the main characters, Carl Fredricksen and Russell. Drawing on Grice’s theory of conversational implicature, this research distinguishes between generalized conversational implicature and particularized conversational implicature. Employing a descriptive qualitative method, the data were collected from selected dialogue transcripts and analyzed based on their contextual meanings. The findings reveal that both types of conversational implicature occur in the film; however, particularized conversational implicature appears more frequently than generalized conversational implicature. This dominance indicates that the interpretation of meaning in the film’s dialogues largely depends on specific situational and relational contexts. The study demonstrates that conversational implicature plays an important role in conveying character relationships, emotional depth, and narrative development in animated films.